FOOD DONATION TO HOMELESS PEOPLE: A NARRATIVE REVIEW - da Costa, Bruna Debortoli Miranda; Tuyama, Ester Batista; Santos, Gabriel Gomes de Morais; Amaral, Gustavo da Silva; Ribeiro, Marcus Eduardo Coutinho; de Souza Junior, Valdeir Wallace; Miranda, Yuri Rodrigues; Barros, Eunice da Silva (Seven Editora, 2025)
This narrative review article addresses the impact of food donation to homeless people, analyzing practices that transcend welfare and promote Food and Nutrition Security. The research was conducted through the analysis of academic literature published between 2019 and 2024 in databases such as Scielo and PubMed. The data were organized around two guiding questions: i) Food donations in the Promotion of Food Security for Homeless People: Government programs and Solidarity Kitchens; ii) Evaluation of products donated to homeless people. The results indicate that, although donations are essential to reduce hunger, much of the donated food is ultra-processed and nutritionally inadequate, which aggravates health problems such as malnutrition and chronic diseases. On the other hand, solidarity kitchens, which offer balanced and fresh meals, prove to be effective alternatives, as they promote improvements in quality of life and food security. The review concludes that conscious donation is essential to mitigate nutritional inequalities and highlights the importance of public policies, nutritional education, and sustainable initiatives to promote adequate and dignified food for vulnerable populations. DOI: https://doi.org/10.56238/sevened2024.037-157